2016
DOI: 10.1113/jp271930
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectric signalling via potassium channels: a mechanism for craniofacial dysmorphogenesis in KCNJ2‐associated Andersen–Tawil Syndrome

Abstract: Key pointsr Xenopus laevis craniofacial development is a good system for the study of Andersen-Tawil Syndrome (ATS)-associated craniofacial anomalies (CFAs) because (1) Kcnj2 is expressed in the nascent face; (2) molecular-genetic and biophysical techniques are available for the study of ion-dependent signalling during craniofacial morphogenesis; (3) as in humans, expression of variant Kcnj2 forms in embryos causes a muscle phenotype; and (4) variant forms of Kcnj2 found in human patients, when injected into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
148
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 152 publications
4
148
0
Order By: Relevance
“…First, we detected expression of the voltage-gated potassium channel Kcnh7 and the A-type current regulator Kcnip1 in this late ectoderm program. This finding is consistent with a role for potassium currents in craniofacial patterning (Adams et al, 2016; Dahal et al, 2012), and provides a specific temporal focus for electrical excitability in patterning the ectoderm. Second, the Gaba receptor A, Pi subunit (Gabrp) was highly expressed in ectoderm from E11.5 and E12.5 (e.g.…”
Section: Resultssupporting
confidence: 86%
“…First, we detected expression of the voltage-gated potassium channel Kcnh7 and the A-type current regulator Kcnip1 in this late ectoderm program. This finding is consistent with a role for potassium currents in craniofacial patterning (Adams et al, 2016; Dahal et al, 2012), and provides a specific temporal focus for electrical excitability in patterning the ectoderm. Second, the Gaba receptor A, Pi subunit (Gabrp) was highly expressed in ectoderm from E11.5 and E12.5 (e.g.…”
Section: Resultssupporting
confidence: 86%
“…The specific role of Kir 2.1 during craniofacial development was addressed more recently. In Xenopus , kcnj2 is initially expressed at early neurula stage (NF stage 14) in a broad dorso-anterior domain, which later becomes regionalized anteriorly, consistent with a potential role in craniofacial morphogenesis [92]. Previous studies from this group showed that there is a unique pattern of membrane resting potential (V mem ) in the ectoderm of the embryo that is critical to maintain gene expression domains as development progresses [93].…”
Section: Craniofacial Disorders Modeled In Xenopusmentioning
confidence: 99%
“…Injection of either wild-type (WT) Kcnj2 or a variant carrying one of the known ATS mutations led to changes in the normal pattern of V mem at the neurula stage, and resulted in craniofacial anomalies at the tadpole stage. However, Kcnj2 mutant proteins caused defects at a higher frequency than the WT [92]. The craniofacial anomalies observed in these tadpoles included misshapen eyes, small or bent Meckel’s cartilage, undersized branchial arches and pigmented optic nerve.…”
Section: Craniofacial Disorders Modeled In Xenopusmentioning
confidence: 99%
See 2 more Smart Citations